PERTUMBUHAN JUMLAH DAUN TANAMAN SAMBILOTO (Andrographis paniculata. Ness) HASIL PEMBERIAN PUPUK DAN INTENSITAS CAHAYA MATAHARI YANG BERBEDA - Malik, Nurhayu (Jurnal BioWallacea, 2015)
This study aims to evaluate the effect of fertilization and different light intensity ongrowth of leaf number plant (Andrographis paniculata Ness). The study was conducted usingCompletely Randomized Design (CRD) with factorial 3 x 3. The main factor is fertilizationtreatment which consist of three levels : NPK (Urea 1.2 grams / plant, TSP 2.4 g / plant andKCl 0.6 g / plant), animal manure (1.2 kg / plant) and without fertilization. The second factoris the different light intensity which consist of three levels: full light intensity, half-shade andfull shade. For Each treatment combination 3 replicates were used. Growth number ofleaves was observed 1 and 2 months after application of fertilizer and light intensity. Datawere analyzed using the Analysis Of Variance (ANOVA). The results obtained showed thatbitter plant leaf number differently to fertilization and different light intensity on plant growth.Aplplication of manure combined with light intensity of 100% gave higher number of leaves.Key words : Growth, leaf number, fertilizers, light intensity